TINJAUAN YURIDIS KONSEP MAKAR DALAM PERSPEKTIF HUKUM TATA NEGARA ISLAM - Syariful Alam (Legality : Jurnal Ilmiah Hukum, 2018)
The treason or treason act is closer to the act of betrayal. In a constitutional law perspective, this treason is defined as the act of a person or group of people towards leadership in a country because of its incompatibility with the rules that apply in the country, so that he or they take actions that tend to "deviate" so that it can break down the leadership of a state leader. In the corner of the desert of Islam, treason or treason act can be done by a person or group of people preceded by a political conspiracy, evil consensus, and intrigue to achieve its political goals. In the Qur'an several verses are mentioned about this treason. Where all contain the notion that treason is an act or an attempt to oppose and undermine the power of someone who is not favored or considered an enemy who has conflicting indications. Both in terms of religion and worldliness by means of deception, deception, or other acts that are contrary to the religion of Islam. Starting from this context, the author wants to review specifications and indications of treason from the perspective of Islamic state governance law by taking the constellation of thoughts of classical scholars.